14.57 Expanding the phenotypic spectrum of PSP: Findings from the PROSPECT-UK study. Issue 12 (14th November 2019) - Jabbari, Edwin; Woodside, John; Costantini, Alyssa; Lees, Andrew; Morris, Huw
Abstract : Background: Progressive supranuclear palsy (PSP) is a common cause of atypical parkinsonism. Objective: To study the genetic and clinico-pathological profile of various PSP phenotypes using patient data from the PROSPECT-UK study. Methods: Clinical data from PSP patients in the PROSPECT-UK study was analysed to assess the rates of various PSP phenotypes, as defined by the 2017 Movement Disorder Society diagnostic criteria. A subset of patients are currently undergoing 5 year longitudinal follow-up, including genetics, video clinical assessments and post-mortem confirmation of diagnosis. Results: We have established a cohort of 345 patients with PSP. The longitudinal sub-cohort consists of 100 PSP patients: 58 patients with classical Richardson's syndrome (RS) and 42 patients with a variety of non-RS presentations including PSP-Parkinsonism and Pure Akinesia with Gait Freezing. We found significant differences in the mean disease duration of deceased RS and non-RS cases (5.6 vs 9.2 years) but similar rates of PSP pathology in cases (n=28) with post-mortem confirmation (94% and 100%). Our PROSPECT-UK data has contributed to a GWAS which identified that common variation at the TRIM11 locus determined PSP phenotype (Jabbari et al 2018). In addition, we have identified 1 case with a MAPT L284R mutation and 1 case with genetic and biochemically confirmed Niemann-Pick type C disease. Conclusions: The PROSPECT-UK study has furthered our knowledge on the clinical profile of PSP and the biological determinants which drive phenotypic variation.